Housing Paul and Paula: Building Repair and Urban Renewal in the German Democratic Republic. Issue 1 (12th June 2019) - Putz, Andreas W.
Abstract : This article traces the re-emergence of historic forms in 20th-century architecture to approaches embedded within the modern project itself. As the history of modern architecture has focused on the production of the new, the resilience of the existing built environment and the implications of appropriating older structures for architectural development are often neglected. The article will look at formerly socialist East Germany, where the grand narrative of modernity was underpinned by a determinist worldview and an ideological urge to replace a doomed capitalist past with a promising socialist future. But despite the intentions of the socialist regime, the existing built environment in East Germany could not be immediately replaced. The old structures had to remain in continuous use. As exemplified by the notable work of Bernhard Klemm, East German architects attempted to recover the built environment in the GDR. To manage the building stock within the constraints of a centrally planned economy, they applied principles of industrial organization and industrial building technologies. Although these primarily local approaches could not entirely prevent dilapidation, the rationalization and industrialization of building repair and urban renewal resulted in the scientific idea of reproducibility and in a reappropriation of historic forms.